Supporting Youth Participation in Health and Climate Justice Through Advocacy Training; Comment on "Between Rhetoric and Reality: Learnings From Youth Participation in the Adolescent and Youth Health Policy in South Africa" - L. Katie O'Connell; Nisha Botchwey (Kerman University of Medical Sciences, 2023)
This paper responds to lessons from the Adolescent and Youth Health Policy (AYHP) process in South Africa by drawing comparisons with youth participation within the climate justice movement. Relationship building is essential to successful youth participation in health policy and climate change as it creates intergenerational learning and cross-cultural engagement. At the same time, both sets of youth also deal with compounding challenges due to contemporary and historical legacies of colonialism and inequality. Yet, tokenism challenges the participatory process as adults profess to value youth perspectives, yet recommendations by youth often do not get incorporated into policies or plans. For organizations and agencies trying to build youth's capacity, organizations and agencies should look to programs that train youth in advocacy. These programs help build youth's confidence, increase their optimism for change, and give youth a sense of ownership.